What are the origin and route of diseases in Iran? - Mahdi Balalimood (مجله دانشگاه علوم پزشکی بیرجند, 2023)
Since the gens change due to the environmental and individual factors, the role of these factors is now more important for the human health. In countries that the facilities such as clean air, healthy water and food, sport and recreational sites, social security and disease prevention programs readily available for all, the society is healthy and happy. Thus, the overall morbidities and mortalities have been declined. ‌But unfortunately, in some countries like Iran that has not paid attention to these factors, the overall morbidities and mortalities have been increased.